THE HYDROALCOHOLIC EXTRACT OF ROSMARINUS OFFICINALIS ATTENUATES LIVER DAMAGE AFTER BILE-DUCT LIGATION IN RATS - H. Sadeghi#; N. Azarmehr#; M. Mansourian; B. Khalvati; E. P. Kokhdan; Z. Salehpour; A. Asfaram; A. H. Doustimotlagh (Journal of Animal and Plant Sciences, 2020)
The aim of the present study was to investigate the possible hepatoprotective effects of hydroalcoholic extract of Rosmarinus officinalis (RO) against liver damage in bile duct ligation (BDL)-induced cholestatic rats. Thirty-four male Wistar rats (225± 25 g) were randomly divided into four groups; sham control (SC, N=7), BDL (N=9), BDL+ 500 mg/kg/day hydroalcoholic extract of RO (N=9), and BDL+ 50 mg/kg/day silimarin (N=9). Two weeks later, the rats were sacrificed, the blood and liver were collected for liver enzyme, plasma and hepatic oxidative stress markers, antioxidant enzymes activity and hematoxylin and eosin staining. The BDL model significantly elevated the plasma oxidative stress markers and liver enzymes, as well as decreased the liver total thiol and ferric reducing antioxidant power as compared to SC group (p≤0.05). Hydroalcoholic extract of RO and silimarin significantly reduced liver enzymes and histology indices (p≤0.05), however, they did not show a significant effect on oxidative stress markers. It was concluded that the hydroalcoholic extract of Rosmarinus officinalis has a hepatoprotective effect on liver damage in rats induced by BDL.
Keywords: Liver; Cholestasis; Bile duct ligated; Rosmarinus officinalis